Sustainable Marketing: How eco-labeling affect consumer preferences in food industry - Baitabenova, T.N.; Orazbayeva, T.M.; Shamardanova, A.N.; Zhanabylova, I.A. (International School of Economics KAZGUU, Nur-Sultan, 2022)
This paper is focused on the issue of how eco-labeling affects consumer preferences. The purpose of this study is to identify the effect of eco-labeling to consumers’ purchase decisions when buying food products in Nur-Sultan in the context of sustainable consumption. Since customers are one of the most powerful forces and crucial parts of sustainable marketing, the study will be supported by data from an online survey conducted among the residents of Nur-Sultan city as well as articles from past literature in this field. The quantitative method was used and 206 respondents were interviewed, of which almost 32% buy eco-products on a permanent basis and the same amount are concerned about environmental problems. Based on research findings and previous literature, it was revealed that consumers are highly involved in the buying process of food and pay attention to the presence of eco-labels and composition. Consumers' awareness of sustainable consumption influences their choice during buying food products with eco labeling in the city of Nur-Sultan.
Keywords: Sustainable Marketing